Effect of Product Quality, Price Perceptions and Brand Image on Purchase Decisions - Hartatik, Hartatik; Sutardjo, Agus; Putra, I Gusti Ngurah Agung Dewantara; Hasan, Syahril; Sugianto, Efendi (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Sidomuncul is a herbal medicine industry that is currently very developed. Consumers in making choices are influenced by various factors. This research aims to determine the influence of product quality, price perception and brand image on purchasing decisions. The case study for this research is consumers of Sidomuncul wind resistance products. This research method is quantitative using primary data sourced from questionnaires. The number of respondents for this research was 100 respondents. The results of this research show that product quality, price perception and brand image influence purchasing decisions.